Epidemiological and Clinical Insights into Acinetobacter baumannii: A Six-Year Study on Age, Antibiotics, and Specimens - Almoghrabi Y; Daghistani H; Niyazi HA; Niyazi HA; AbdulMajed H; Juma NA; Daffa N; Helmi NR; Al-Rabia MW; Mokhtar JA; Saleh BH; Attallah DM; et al. (International Journal of General Medicine)
Yousef Almoghrabi,1,2,* Hussam Daghistani,1,2,* Hanouf A Niyazi,3,* Hatoon A Niyazi,3,* Hind AbdulMajed,3,* Noha A Juma,3,* Noura Daffa,3,* Noof R Helmi,3,* Mohammed W Al-Rabia,3,4,* Jawahir A Mokhtar,3,5,6,* Bandar Hasan Saleh,3,* Dalya M Attallah,5 Maram Matar,5 Hani Ahmed Shukri,5 Shahd A Moqaddam,5 Sara Alamoudi,5 Khalil K Alkuwaity,6,7,* Turki Abujamel,6,7,* Ahmad M Sait,2,7 Mohammed Mufrrih,7,8 Ibrahim A Al-Zahrani,7,8,* Stephen O’hagan,9 Mazen A Ismail,10,* Ohood S Alharbi,11,* Hattan Jamal Momin,12,* Ibrahim Mohammed Abu,13,* Abdelbagi Alfadil,3,4,* Karem Ibrahem3 1Department of Clinical Biochemistry, Faculty of Medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 2Regenerative Medicine Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 3Department of Clinical Microbiology and Immunology, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 4Centre of Research Excellence for Drug Research and Pharmaceutical Industries, King Abdulaziz University, Jeddah, Saudi Arabia; 5Department of Clinical Microbiology Laboratory, King Abdulaziz University Hospital, Jeddah, 21589, Saudi Arabia; 6Vaccines and Immunotherapy Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 7Department of Medical Laboratory Sciences, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 8Special Infectious Agents Unit BSL-3, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, Saudi Arabia; 9Department of Chemistry, Manchester Institute of Biotechnology, The University of Manchester, Manchester, UK; 10Department of Medical Education, Faculty of Medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 11Department of Microbiology and Parasitology, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 12Medical Service Center, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 13Department of Community Medicine, Faculty of Medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia*These authors contributed equally to this workCorrespondence: Karem Ibrahem, Email kaibrahem@kau.edu.saBackground: This six-year retrospective study provides an in-depth analysis of the epidemiological and clinical patterns associated with Acinetobacter baumannii (A. baumannii) infections, focusing on age distribution, antibiotic resistance profiles, and specimen types.Aim: The research examines the incidence and characteristics of both non-Multi-Drug Resistant (non-MDR) and Multi-Drug Resistant (MDR) A. baumannii strains by reviewing patient records from January 2016 to December 2022.Methods: Through a statistical analysis, the study highlights the incidence rates across diverse age groups and explores the impact of antibiotic treatment regimens on infection outcomes. Additionally, it identifies the primary clinical specimen types for each strain, noting an association between non-MDR A. baumannii and midstream urine samples, while MDR A. baumannii strains were more frequently found in respiratory, wound, peripheral, and central line swaps/specimens.Results: The results indicate that in 2016, non-MDR A. baumannii infections were notably more frequent compared to MDR A. baumannii cases. However, a significant shift occurred in 2021 and 2022, with a marked decrease in non-MDR A. baumannii cases and an increase in MDR A. baumannii infections. Antibiotic susceptibility testing revealed that non-MDR strains were commonly tested against cefazolin, ceftazidime, ciprofloxacin, gentamicin, nitrofurantoin, oxacillin, piperacillin/tazobactam, and trimethoprim/sulfamethoxazole. In contrast, MDR strains were frequently tested against amikacin, cefepime, colistin, meropenem, imipenem, and tigecycline.Conclusion: This study enhances the understanding of A. baumannii clinical behaviour and resistance patterns, offering valuable insights to support future research and inform strategies for infectious disease management and control.Keywords: Acinetobacter baumannii, MDR, the epidemiological and clinical patterns